Inquérito sorológico da língua azul em ovinos de Minas Gerais - Biihrer, Daniel Arrais (2017)
Bluetongue is an infectious, non-contagious disease that affects domestic and wild ruminants, caused by a vírus from Orbivirus genus, Reoviridae family, transmitted by arthropod vectors of the Culicoides genus. There are reports of clinical disease in sheep that occurred in several states of Brazil, including Minas Gerais. This paper aims to be the first serological survey of bluetongue in sheep from the Meso-regions of Campo das Vertentes and South and Southeast of Minas Gerais. Samples were collected from sheep from different properties, in which epidemiological questionnaires were also applied. The serum samples were submitted to Agar Gel Immunodiffusion (AGID) and competitive Enzyme Linked Immunosorbent Assay (cELISA). Epidemiological data were related to positive animals by statistical analyzes. A total of 303 serum samples were submitted AGID and cELISA. In these samples, 164 (54.13%) were positive in the AGID technique and 171 (56.44%) positive in the cELISA technique, with almost perfect agreement between the techniques (kappa index = 0.887). In all visited properties positive animals have been found in the herd. Animals acquired from properties of the studied Meso-regions were more likely to be positive in IDGA and cELISA tests than animals acquired from properties in other regions of Brazil (p <0.001), showing that the virus circulates in an important way on the studied Meso-regions. As expected in a region in with increased circulation of the virus, most of the animals positives in the serological tests didn’t show any clinical signs. These results suggests that bluetongue virus is widespread in the Meso-regions of Campo das Vertentes and South and Southeast of Minas Gerais, mostly causing subclinical infections.